Effect of water parameters on temporal distribution and abundance of zooplankton at Kaptai lake reservoir, Rangamati, Bangladesh (Asian Journal of Medical and Biological Research, 2018)
Seasonal abundance of zooplankton in relation to different physico-chemical conditions of Kaptai lake has been studied. A total of four major groups of zooplankton were identified from study area of Kaptai lake during three seasons observation at pre-monsoon, monsoon and Post-monsoon. These four groups were categorized into rotifers, copepods, cladocerans and others (fish larvae, shrimp larvae, insects, mosquito larvae etc.). The mean abundance of group rotifers, copepods, cladoceras and others were 103, 84.67, 38.33 and 41.83 ind. L-1 respectively. The highest group was rotifers in terms of abundance and composition where compositions were recorded 38 % at three season’s observation. The lowest group was cladoceras in term of abundance and composition where compositions were recorded 14 %. The air temperature, water temperature, transparency, water pH, DO, BOD5, PO4-P, NO2-N, SiO3-Si, TSS, TDS, Alkalinity ranged between 21 and 27.50C, 23.5 and 31.50C, 0.8 and 3 m, 7.1 and 7.5, 5.72 and 8.58 mg/l, 8.55 and 12.87 mg/l, 3.22 and 4.13 μg/l, 0.992 and 1.19 μg/l, 161.18 and 201.15 μg/l, 0.28 and 0.48 g/l, 0.18 and 0.68 g/l, 40 and 60 ppm, respectively. Margalef richness index (d), Pielou’s evenness index (J'), Shannon-Wiener diversity index (H'), Simpson dominance index (λ) are analyzed by Primer V6 software to quantify the collected species. Through same software SIMPER, Cluster analysis also done to compare similarity between season.Asian J. Med. Biol. Res. December 2018, 4(4): 389-399